THE EFFECT OF COCONUT SHELL LIQUID SMOKE APPLIED AT VARIED CONCENTRATION AND SOAKING TIME ON THE QUALITY OF SMOKE FLAVORED CATFISH (Cryptopterus bicirchis) - wahyuni, Sri; Mus, Sukirno; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of the research was to evaluate the quality of smoke flavored catfish (Cryptopterus bicirchi) produced by liquid smoking. The method used was experimental, designed as Completely Block Randomized Design (CBRD) and composed factorially 4x2. The catfish was eviscerated and then soaked in a solution of coconut shell liquid smoke at different concentration, namely: 2% (K2), 4% (K4), 6% (K6), 8% (K8), combined with second treatment factor, that was fish soaking time in the liquid smoke for 60 minutes (L60) and 90 minutes (L90). 4% (K4), 6% (K6) and 8% (K8) for 1 hour (L1) and 2 hours (L2). After soaked, the fish were then dried using an oven at the temperature of 55o C for 12 hours and then stored and observed for 36 days at room temperature. The results showed that smoke flavored catfish produced by soaking the fish into liquid smoke at the concentration of 6% for 60 minutes (K6L60) was the most preferred by panelists. The best smoke flavored catfish was showing the highest score of appearance 7,78; score of taste 7,9; score of texture 8,1. At the last day of the storage, the chemical and microbial characteristics of the product was consisted of TBA concentration 2.13, content of total acid 99.7, total phenol 6.7, moisture 7,2% and TPC 3,73 cfu/g.Keywords: liquid smoke, smoke flavored catfish, soaking time